Effect of Yikou-Sizi powder hot compress on gastrointestinal functional recovery in patients after abdominal surgery: Study protocol for a randomized controlled trial. Issue 38 (September 2018) - Cao, Lixing; Wang, Tao; Lin, Jinxuan; Jiang, Zhi; Chen, Qicheng; Gan, Huachan; Chen, Zhiqiang
Abstract: Background: Postoperative gastrointestinal dysfunction (PGD) is a common complication of patients who have undergone surgery. The clinical manifestations cause great discomfort to postoperative patients and can severely affect postoperative recovery. However, although various pharmacologic agents have been explored for several years, success has been limited. Because some commonly used drugs have caused adverse reactions and because abdominal surgery patients generally cannot consume food or medication during the perioperative period, we were prompted to try an external Chinese medicine treatment method. Yikou-Sizi powder hot compress is an efficient therapy in our hospital, but there is a lack of rigorous studies to certify the safety and effectiveness of its external use to improve gastrointestinal motility. This study aimed to introduce the clinical trial design and test the ability of Yikou-Sizi powder hot compress treatment to accelerate gastrointestinal functional recovery after abdominal surgery. Methods: This study is a randomized controlled clinical trial. The participants will undergo laparoscopic colorectal cancer surgery and laparoscopic total hysterectomy. The primary outcome measure will be the gastrointestinal functional evaluation index, including the time to first passage of flatus, first defecation, first normal bowel sounds, and first consumption of liquid/semigeneral diet foods. According to good clinical practice (GCP), we will evaluate the clinical efficacy and safety of Yikou-Sizi powder hot compress and objectively study the acting mechanism of ghrelin. This pilot trial will be a standard, scientific, and clinical study designed to evaluate the effect of Yikou-Sizi powder hot compress for the recovery of gastrointestinal function after surgery and determine its overall safety. Discussion: This is the first study to describe the use of Yikou-Sizi powder hot compress to accelerate the recovery of gastrointestinal function after abdominal surgery. The study is designed as a randomized, controlled, clinical, large sample size and pilot trial. Evaluation will consist of combining the primary outcome measures with secondary outcome measures to ensure the objectivity and scientific validity of the study. Due to the observational design and the limited follow-up period, it is not possible to evaluate to what extent the connection between the observed improvement and the interventions represents a causal relationship. Efficient comparison between groups will be analyzed by chi-square test.